Implementasi Pendidikan Karakter Peserta Didik Kelas V Madrasah Ibtidaiyah Darunnajah 2 Cipining Bogor - Wibowo, Muhammad Zusril; Ghifari, Abudzar Al; Kurniawan, Muhammad Irfanudin; Farid, Ahmad (Universitas Nusantara PGRI Kediri, 2023)
Character education has been rolled out since 2010 and is still valid today. In character education there are several values, one of which is responsibility. The character of responsibility is very important so that the school becomes a self-development institution to achieve success. Depletion of awareness and even loss of the character of responsibility in students which hinders learning activities so that this should not happen. This study focuses on definitions, benefits, and strategies in learning to improve the character of student responsibility in schools. The results of this study include: 1) character refers to a series of attitudes, behaviors, motivations, and skills while the character of responsibility is the attitude and behavior of a person to carry out his duties and obligations which he should do towards himself, society, the environment (natural, social and cultural), the State and God Almighty; 2) the benefits of the character of responsibility are that it can improve the quality of learning in the classroom and can improve school quality standards; 3) the character of responsibility can be done with a mind mapping strategy, inquiring mind what to know, CRH, NHT, and Quiz Team. This study concludes that the character of responsibility and learning must be carried out as one of the character education in schools through several strategies.